ScamNet: Toward Explainable Large Language Model-Based Fraudulent Shopping Website Detection - Bitaab, Marzieh; Karimi, Alireza; Lyu, Zhuoer; Mosallanezhad, Ahmadreza; Oest, Adam; Wang, Ruoyu; Bao, Tiffany; Shoshitaishvili, Yan; Doupé, Adam (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Fraudulent shopping websites pose a significant threat to online consumers and legitimate businesses: in 2023, victims of such scams reported $392 million in losses to the Federal Trade Commission. This alarming trend not only impacts individuals but also erodes societal trust in e-commerce, necessitating urgent countermeasures. While previous studies have attempted to identify these fraudulent websites at scale, they face limitations such as potential bias in data collection, overreliance on easily manipulated features, and the lack of explainable results. This study explores the potential of Large Language Models (LLMs) in identifying fraudulent shopping websites, revealing that current LLMs underperform compared to existing machine learning models. To address this, we propose ScamNet, a fine-tuned LLM for explainable fraudulent shopping website detection. Our experimental results on real-world datasets demonstrate a breakthrough in detection performance from 22.35% detection rate to 95.59%, particularly in identifying subtle deceptive tactics such as using a legitimate-looking website template. ScamNet offers interpretable insights into its decision-making process, enhancing transparency and overcoming a key limitation of previous approaches.